IMAM NASAI'S LIFE AND SCIENTIFIC ACTIVITY - Usmanov Mahammadsiliq Abdumannonovich (Bright Mind Publishing, 2025)
In this article, there will be a specific data about Imam Nasai, who was one of the most famous of six narrators in the Islamic world. Furthermore there will be some information about the Narrator’s life path, teachers, apprentices, also his scientific researches and his portion in terms of developing scientific hadith.
Keywords: Golden age,